APPLICATION OF MODERN METHODS IN TEACHING ENGLISH - Boyxanova, Nilufar Ravshanbekovna (Educational Research in Universal Sciences, 2023)
One of the most crucial components of tolerance in a personality culture is language learning. Since language is a tool for communication, it can be learned nearly anywhere in the home, in the community, or in a formal setting. Additionally, theory-based instruction is given on language phenomena. Language proficiency, especially multilingualism, is extremely important in today’s world of active international interactions. In our country, most pupils and foreign students learn three languages. Special names are used to identify these languages. Native language, second language, and foreign language are these. The first language that functions independently in the development of thinking is the native tongue. The second language is treated as the language of its fraternity, or neighbors, which are made up of people from various nationalities when it is spoken. In this article, opinions and feedback on the use of modern methods in teaching English are kept.